The Implementation of ‘Alpukat Betawi’ as a Public Service Innovation - Vicky Zaynul Firmansyah; Muhammad Maulana; Mary Ismowati (Universitas Sebelas Maret, 2022)
The Jakarta Smart City Plan is an effort by the DKI Jakarta Provincial Government to use information technology in government sectors. One of the strategies developed by DKI Jakarta Provincial authorities, especially at the Department of Population and Civil Registration is the Alpukat Betawi (Direct Access to Fast and Accurate Population Documentation Service) app. This application provides various access to population licensing services and civil registration for residents of Jakarta. The purpose of this study is to analyze the implementation of e-government in the provision of public services within the framework of population administration services. Descriptive qualitative methods were used in this study. The data comes from a literature study, the results of observations and interviews. The results show that the use of the Alpukat Betawi app is not yet optimal. It has been found that limitations and barriers lead to people not knowing and understanding how to access online administrative services, lack of socialization of online application based systems, synchronization of population databases remains weak, and lack of human resources and IT system facilities due to budget constraints. This research will provide recommendations to improve the public service system to increase accountability, professionality, effectiveness and transparency of public services. In this case, DKI Jakarta Provincial of The Department of Population and Civil Registration should take action to plan, develop, and innovate in improving population online services and increasing civic engagement.